2020
DOI: 10.1111/1440-1681.13378
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bleomycin‐induced oxidative stress and pulmonary fibrosis by N‐acetylcysteine in rats via AMPK/SIRT1/NF‐κβ

Abstract: The efficacy of bleomycin (BLM) as an antineoplastic drug is limited to the development of dose and time‐dependent pulmonary fibrosis. This study was intended to investigate the effect of N‐acetylcysteine (NAC) on BLM‐induced pulmonary fibrosis in rats. Twenty rats were randomly divided to the following four groups: Group one served as control; group two received BLM (15 mg/kg, intraperitoneal (ip)) for five consecutive days; group three received NAC (200 mg/kg, ip) for five consecutive days; and group four re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Moreover, PF 50 restrained BM-induced lung damage, which is a major cause of COVID-19 patients' deaths. It is evidenced that all of the COVID-19 lung pathogenesis has been experimentally verified in the BM model [51] , [52] , [53] , [54] , [55] , which is consistent with our results. Compared with other organs, the lungs are more vulnerable to BM toxicity because of their lack of a BM-hydrolyzing enzyme [56] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, PF 50 restrained BM-induced lung damage, which is a major cause of COVID-19 patients' deaths. It is evidenced that all of the COVID-19 lung pathogenesis has been experimentally verified in the BM model [51] , [52] , [53] , [54] , [55] , which is consistent with our results. Compared with other organs, the lungs are more vulnerable to BM toxicity because of their lack of a BM-hydrolyzing enzyme [56] .…”
Section: Discussionsupporting
confidence: 92%
“…BM directly generates ROS upon its simultaneous binding to Fe (II) and DNA in the presence of oxygen, resulting in iron oxidation and DNA breakage that ultimately leads to caspase-dependent apoptosis [53] , [57] . In harmony with these studies and many others [54] , [58] , the BM-exposed LTC-A549 cell line (the best model of ATII cells) in our research had high levels of ROS and apoptosis and a low level of GSH ( Fig. 6 “a-c”).…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, it is reasonable to believe that renalase's ability to fine-tune pleiotropic proteins, SIRT1 [19] and SIRT3 [30] regulation during the SARS-CoV-2-related disease, may be an additional factor aiming to inhibit viral reproduction and control inflammation and its consequences. Renalase, however, owing to its efficient sustaining of NAD + levels may control SIRTs-mediated events during coronavirus 2 infection that, as stated, appear to be compelling participants in both inflammatory and fibrotic stages of pulmonary fibrosis [123][124][125][126][127][128][129][130]. The discovery of novel molecules, such as renalase, that interfere with SIRTs activities, possibly via regulation of NAD + intercellular levels, providing advantage for sitruins' defense properties, may prove highly relevant against SARS-CoV-2 infection [121].…”
Section: Protection Against the Progression Of Diabetic Nephropathymentioning
confidence: 96%
“…Indeed, various pharmacological upregulation of SIRT1 demonstrate significant effectiveness in lung protection, through the suppression of excessive inflammatory response, oxidative stress, apoptosis, and fibrosis. SIRTs-mediated mitigation of lung inflammation and cellular senescence is confirmed in settings such as obstructive pulmonary diseases [ 123 ], sepsis-induced acute lung injury [ 124 ], and ARDS [ 125 ]; idiopathic pulmonary fibrosis TGF- β 1-mediated epithelial-mesenchymal transition and alleviation of its progression [ 126 128 ]; oxidative stress; and fibrosis in bleomycin-induced oxidative stress and pulmonary fibrosis [ 129 ], both the early (inflammatory) and late (fibrotic) stages of systemic sclerosis-related pulmonary fibrosis [ 130 ], indicating its potential employment as a therapeutic agent for pulmonary diseases with underlying inflammation.…”
Section: Renalase and Sirtuins Cross-talk In The Context Of Covid-19mentioning
confidence: 99%
“…As an important pathogenetic mechanism, oxidative stress can promote fibrosis by increasing the transformation of fibroblasts to myofibroblast [ 8 ], inducing apoptosis of alveolar epithelial cells, and upregulating the expression of profibrotic cytokines (including TGFs) [ 9 , 10 ]. Moreover, studies have shown that inhibiting oxidative stress can effectively reduce pulmonary fibrosis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%